Elective upper-neck versus whole-neck irradiation of the uninvolved neck in patients with nasopharyngeal carcinoma: an open-label, non-inferiority, multicentre, randomised phase 3 trial - Tang, Ling-Long; Huang, Cheng-Long; Zhang, Ning; Jiang, Wei; Wu, Yi-Shan; Huang, Shao Hui; Mao, Yan-Ping; Liu, Qing; Li, Ji-Bin; Liang, Shao-Qiang; Qin, Guan-Jie; Hu, Wei-Han; et al. (The lancet oncology, 2022)
The aim of this trial was to address whether elective ipsilateral upper-neck irradiation (UNI) sparing the uninvolved lower neck provides similar regional relapse-free survival compared with standard whole-neck irradiation (WNI) in patients with nasopharyngeal carcinoma. This open-label, non-inferiority, randomised, controlled, phase 3 trial was done at three Chinese medical centres. Patients aged 18–65 years with untreated, non-keratinising, non-distant metastatic (M0) nasopharyngeal carcinoma; with N0–N1 disease (according to International Union Against Cancer–American Joint Committee on Cancer TNM classification, seventh edition); and a Karnofsky performance status score of 70 or higher were randomly assigned (1:1) to receive elective UNI or WNI of the uninvolved neck. Total radiation doses of 70 Gy (for the primary tumour volume and the enlarged retropharyngeal nodes), 66–70 Gy (for the involved cervical lymph nodes), 60–62 Gy (for the high-risk target volume), and 54–56 Gy (for the low-risk target volume) were administered in 30–33 fractions, five fractions per week. Patients with stage II–IVA disease were recommended to receive combined intravenous cisplatin-based chemotherapy (either induction chemotherapy followed by concurrent chemoradiotherapy or concurrent chemoradiotherapy alone). Randomisation was done centrally by the Clinical Trials Centre of Sun Yat-sen University Cancer Centre by means of a computer-generated random number code with a block size of four. Patients were stratified according to treatment centre and nodal status. Investigators and patients were not masked to treatment allocation. The primary endpoint was regional relapse-free survival in the intention-to-treat population. Non-inferiority was indicated if the upper limit of the 95% CI of the difference in 3-year regional relapse-free survival between the UNI and WNI groups was within 8%. Adverse events were analysed in the safety population (defined as all patients who commenced the randomly assigned treatment). This study is registered with ClinicalTrials.gov, NCT02642107, and is closed. Between Jan 22, 2016, and May 23, 2018, 446 patients from 469 screened were randomly assigned to receive UNI (n=224) or WNI (n=222). Median follow-up was 53 months (IQR 46–59). 3-year regional relapse-free survival was similar in the UNI and WNI groups (97·7% [95% CI 95·7–99·7] in the UNI group vs 96·3% [93·8–98·8] in the WNI group; difference −1·4% [95% CI −4·6 to 1·8]; pnon-inferiority<0·0001). Although acute radiation-related toxic effects were similar between the groups, the incidence of late toxicity was lower in the UNI group than in the WNI group, including any-grade hypothyroidism (66 [30%] of 222 patients vs 87 [39%] of 221), skin toxicity (32 [14%] vs 55 [25%]), dysphagia (38 [17%] vs 71 [32%]), and neck tissue damage (50 [23%] vs 88 [40%]). No patients died during treatment. After treatment, one patient in the WNI group died from a non-cancer-related cause (dermatomyositis). Elective UNI of the uninvolved neck provides similar regional control and results in less radiation toxicity compared with standard WNI in patients with N0–N1 nasopharyngeal carcinoma. Sun Yat-sen University Clinical Research 5010 Program, the Natural Science Foundation of Guangdong Province, and the Overseas Expertise Introduction Project for Discipline Innovation. For the Chinese translation of the abstract see Supplementary Materials section.